Determination and Prevalence of Some Important Pathogens in Newborn Calf Diarrhea in Bingol and its Surroundings - KEÇECİ, Hakan and GAZİOĞLU, Abdullah and ILGIN, Mehmet and FIRAT, Recep (MAS Journal of Applied Sciences, 2023)
The aim of this study was to determine clinically the prevalence of the most common pathogens causing diarrhea in 120 calves with diarrhea from 0 to 30 days old by rapid diagnostic test (HTT), standard diagnostic methods, and RT-PCR testing. The animal material consisted of diarrheal calves raised in Bingol and its surroundings. Therefore, the infectious agents causing calf diarrhea are proportionally eimeria 20.83%, escherichia coli 17.50%, rotavirus 16.81%, clostridium perfringens 13.27%, cryptosporidium spp 11.67%, coronavirus 9.16% and giardia 3.33%. Mixed cases have also been found. The same is true for the comparison of detection methods, rapid diagnostic tests for rotavirus (17/24-70.83%), coronavirus (7/24-29.16%), molecular analysis rotavirus (20/24-83.33%), coronavirus (11/24-45.83%) diarrhea cases. There was a slight numerical difference between the diagnosis of HTT (12/29-41.38%) and the microscopic diagnosis of cryptosporidium, one of the parasitic factors (14/29-48.27%), but there was no statistical significance (p>0.05). Hence, the diagnostic rate of the rapid detection kit is relatively high. Therefore, it was concluded that understanding the prevalence of identified pathogens and the differences between detection techniques would have important consequences for academic and clinical veterinarians in the field.